2015
DOI: 10.1016/j.jcrc.2015.04.075
|View full text |Cite
|
Sign up to set email alerts
|

A high mean arterial pressure target is associated with improved microcirculation in septic shock patients with previous hypertension: A prospective open-label study

Abstract: Introduction: The effect of mean arterial pressure titration to a higher level on microcirculation in septic shock patients with previous hypertension remains unknown. Our goal is to assess the effect of mean arterial pressure titration to a higher level on microcirculation in hypertensive septic shock patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…Speculatively, the infusion of norepinephrine might reduce vessel density, as vessel density is found to be lower in cardiac surgery patients receiving norepinephrine . In contrast, infusion of norepinephrine has been found to improve microcirculatory variables in septic shock patients during the first 24 hours . Even though patients in the HMAP group in the present study were given more norepinephrine during and after CPB, we found no difference in changes over time, or at each time‐point, in microcirculatory variables between the 2 treatment groups.…”
Section: Discussioncontrasting
confidence: 82%
“…Speculatively, the infusion of norepinephrine might reduce vessel density, as vessel density is found to be lower in cardiac surgery patients receiving norepinephrine . In contrast, infusion of norepinephrine has been found to improve microcirculatory variables in septic shock patients during the first 24 hours . Even though patients in the HMAP group in the present study were given more norepinephrine during and after CPB, we found no difference in changes over time, or at each time‐point, in microcirculatory variables between the 2 treatment groups.…”
Section: Discussioncontrasting
confidence: 82%
“…MAP is regarded as perfusion pressure of the organs required to maintain blood flow and is considered as the most important hemodynamic parameter for the function of the circulation system. MAP is the determinant factor for maintaining cerebral and renal blood flow (6,8).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that arterial blood pressure was independently associated with survival in patients with liver cirrhosis ascites over a period of 1 year (5). MAP was found to return from 65 mmHg to the normal range and to be closely associated with microcirculation improvement (6). A recent research also demonstrated that a history of hypertension serves as a protective factor for liver-associated clinical decompensation and mortality (7).…”
Section: Introductionmentioning
confidence: 98%
“…Oxygen transport occurs in systemic circulation and through diffusion along the oxygen partial pressure gradient in tissues. Microcirculation is important, as it provides oxygen to local tissues and adjusts its distribution to meet oxygen demand [1]. Sublingual microcirculation can be monitored to detect low perfusion associated with severe infection, organ dysfunction due to septic shock, and mortality [2,3].…”
Section: Introductionmentioning
confidence: 99%